2019
DOI: 10.1016/j.chom.2019.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Virome Analysis Sheds Light on Viral Dark Matter in Inflammatory Bowel Disease

Abstract: The human gut virome is thought to significantly impact the microbiome and human health. However, most virome analyses have been performed on a limited fraction of known viruses. Using whole-virome analysis on a published keystone inflammatory bowel disease (IBD) cohort and an in-house ulcerative colitis dataset, we shed light on the composition of the human gut virome in IBD beyond this identifiable minority. We observe IBD-specific changes to the virome and increased numbers of temperate phage sequences in i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
382
5
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(417 citation statements)
references
References 77 publications
27
382
5
3
Order By: Relevance
“…A large study by Norman et al observed disease-specific changes and reduced diversity of the gut virome in both CD and UC, revealing the primary difference in the IBD-associated virome was the increased richness of Caudovirales phages on a taxonomic level; however, the exact viruses that may give rise to such change were different in CD when compared to UC [88]. A dataset used for this study was recently reanalyzed, confirming IBD-specific changes in the virome, loss of the "core phageome" and increased abundance of induced temperate phages in patients with CD [84]. However, in contrast to the previous report, no changes in viral richness and overall viral alpha diversity were demonstrated.…”
Section: Human Viromementioning
confidence: 60%
See 2 more Smart Citations
“…A large study by Norman et al observed disease-specific changes and reduced diversity of the gut virome in both CD and UC, revealing the primary difference in the IBD-associated virome was the increased richness of Caudovirales phages on a taxonomic level; however, the exact viruses that may give rise to such change were different in CD when compared to UC [88]. A dataset used for this study was recently reanalyzed, confirming IBD-specific changes in the virome, loss of the "core phageome" and increased abundance of induced temperate phages in patients with CD [84]. However, in contrast to the previous report, no changes in viral richness and overall viral alpha diversity were demonstrated.…”
Section: Human Viromementioning
confidence: 60%
“…Accordingly, there is mounting evidence that the community of phages in the gut is altered when dysbiosis-related disorders are considered, such as IBD and colorectal cancer. In addition, a shift from lysogenic to lytic replication in the population of temperate phages may be linked to the development of IBD [84].…”
Section: Human Viromementioning
confidence: 99%
See 1 more Smart Citation
“…This statistic takes into account both mean value and covariance matrix, which makes it suitable for reducing two or high dimensional microbial data into a one-dimensional data containing both abundance and relationship information. The T 2 statistic is the multivariate counterpart of the t statistic and widely used in multivariate process consistence monitoring in both industry and biology fields [25,26]. It can be viewed as the generalized distance between the observed vector from the mean vector weighted by the inversion of covariance 5 matrix, − $ & − [27].…”
Section: Pm2ra Methodsologymentioning
confidence: 99%
“…Some hypotheses provided explanations on the basis of experimental data. For instance, Clooney et al hypothesized that one of the conditions contributing to a healthy colon is the presence of a "healthy" core virome [40]. They performed a whole-virome analysis on two IBD virome datasets, one being an in-house UC cohort and the other being a dataset published by Norman et al [29].…”
Section: Phage Life Cycle In Ibdmentioning
confidence: 99%